Endogenous Quality Effects of Trade Policy - Jose Luis Moraga; Jean-Marie Viaene (Tinbergen Institute, 1999)
We study the optimal trade policy against a foreign oligopoly withendogenous quality. We show that, under the Most Favoured Nation(MFN) clause, a uniform tariff policy is always welfare improvingover the free trade equilibrium. However, a nonuniform tariff policyis always desirable on welfare grounds. First best policy typicallyconsists of setting a subsidy on the low-quality product and a tax onhigh-quality one. Another example of such a nonuniform tariff policyis a Regional Trade Agreement (RTA). We show that, if a welfareimprovement is possible through a RTA, it is always with the low-quality producing country that it has to be achieved.
Keywords: F12; F13; F15; 330; Endogenous Quality; Hedonic Prices; Most Favored Nation (MFN) clause; Optimal Tariff; Regional Trade Agreement (RTA); Außenwirtschaftspolitik; Produktqualität; Hedonischer Preisindex; Zollpolitik; Theorie